Primary total hip replacement using Burch-Schneider cages for acetabular fractures. Issue 3 (May 2022) - Liaw, Frank; Govilkar, Siddharth; Banks, Daniel; Kankanalu, Pradeep; Youssef, Bishoy; Lim, Justin
Introduction: Osteoporotic acetabular fractures are common and pose a difficult technical challenge for the trauma surgeon. Acute total hip arthroplasty (THA) using a Burch-Schneider antiprotrusio cage with immediate postoperative weight-bearing is a method to approach these injuries. This case series reports our outcomes of acute THA using Burch-Schneider cages for acetabular fractures from a UK major trauma centre based on length of stay, radiological outcome, complications and outcome scores. Methods: Data were collected from all patients who underwent acute THA with a Burch-Schneider cage for acetabular fractures between June 2006 and August 2015. Patients were followed up clinically, radiologically, and using Oxford Hip Scores (OHS). Results: 20 patients with a median age of 73 (range 60–90 years) were identified. All patients were independent walkers at follow-up, and had achieved radiological union. There were no dislocations, subsidence, revision or deep infections. Significant complications include 1 perioperative death as a result of complications arising from pre-existing pulmonary fibrosis; 1 deep vein thrombosis; 1 intraoperative arterial injury to the superior gluteal artery; and 1 leg-length discrepancy. Mean length of stay was 10 days. The mean OHS was 37/48 at a mean follow-up of 26 months. Conclusions: This case series further validates the use of Burch-Schneider cages with primary THA in acute acetabular fractures.